Muscle metabolism and fatigue during simulated ice hockey match-play in elite player - Vigh-Larsen, J. F.; Ermidis, G.; Rago, V.; Randers, M. B.; Fransson, D.; Nielsen, J. L.; Gliemann, L.; Piil, J. F.; Morris, N. B.; de Paoli, F. V.; Overgaard, K.; Andersen, T. B.; et al. (Medicine & Science in Sports & Exercise, 2020)
Purpose: The present study investigated muscle metabolism and fatigue during simulated elite male ice hockey match-play. Methods: Thirty U20 male national team players completed an experimental game comprising three periods of 8 × 1-min shifts separated by 2-min recovery intervals. Two vastus lateralis biopsies were obtained either during the game (n = 7) or pregame and postgame (n = 6). Venous blood samples were drawn pregame and at the end of the first and last periods (n = 14). Activity pattern and physiological responses were continuously monitored using local positioning system and heart rate recordings. Further, repeated-sprint ability was tested pregame and after each period. Results: Total distance covered was 5980 ± 199 m with almost half the distance covered at high skating speeds (>17 km·h-1). Average and peak on-ice heart rate was 84% ± 2% and 97% ± 2% of maximum heart rate, respectively. Muscle lactate increased (P = 0.05) more than fivefold and threefold, whereas muscle pH decreased (P = 0.05) from 7.31 ± 0.04 pregame to 6.99 ± 0.07 and 7.13 ± 0.11 during the first and last periods, respectively. Muscle glycogen decreased by 53% postgame (P = 0.05) with ~65% of fast- and slow-twitch fibers depleted of glycogen. Blood lactate increased sixfold (P = 0.05), whereas plasma free fatty acid levels increased 1.5-fold and threefold (P = 0.05) after the first and last periods. Repeated-sprint ability was impaired (~3%; P = 0.05) postgame concomitant with a ~10% decrease in the number of accelerations and decelerations during the second and last periods (P = 0.05). Conclusions: Our findings demonstrate that a simulated ice hockey match-play scenario encompasses a high on-ice heart rate response and glycolytic loading resulting in a marked degradation of muscle glycogen, particularly in specific sub-groups of fibers. This may be of importance both for fatigue in the final stages of a game and for subsequent recovery.